Physicochemical characterization of nimodipine–polyethylene glycol solid dispersion systems. (July 2014) - Barmpalexis, Panagiotis; Kachrimanis, Kyriakos; Georgarakis, Emanouil
Abstract This study investigates the solid–solid interactions between nimodipine (NIM) and polyethylene glycol (PEG) of different mean molecular weights (PEG 2000, 4000 and 6000), in solid dispersion systems, applying differential scanning calorimetry (DSC), Fourier-Transform infrared spectroscopy, powder X-ray diffraction (PXRD), hot stage microscopy (HSM) and theoretical modeling by the Flory–Huggins (FH) solution theory. Phase diagrams constructed with the aid of DSC and FH solution theory showed sensitivity on the estimated values of the FH interaction parameter (χ). When χ is considered a constant number (χ = α, α ≠ 0), formation of a eutectic mixture is predicted in the 70–80% w/w PEG concentration region, while when χ was considered as a function of concentration and temperature (χ = f(φ, Τ)), the model predicts the formation of monotectic systems. Construction of more precise phase diagrams by HSM to the aid of Kofler's "contact preparation" method confirmed the monotectic nature of the examined systems. Studies on NIM's re-crystallization process in the solid dispersions revealed a strong dependence of the crystallization rate, as well as the resulting crystal form, on the mean molecular weight and concentration of PEG: NIM crystallization rates decrease as PEG's MW increases, while NIM mod II crystals predominate in dispersions prepared at temperatures above NIM's liquidus and growth of NIM mod I prevailing in PEG-rich samples.